Genomic Analysis of Antimicrobial Resistance in Pseudomonas aeruginosa from a “One Health” Perspective - Celia García-Rivera; Carmen Molina-Pardines; José M. Haro-Moreno; Mónica Parra Grande; Juan Carlos Rodríguez; Mario López-Pérez (Microorganisms)
The “One Health” approach provides a comprehensive framework for understanding antimicrobial resistance. This perspective is of particular importance in the study of Pseudomonas aeruginosa, as it is not only a pathogen that affects humans but also persists in environmental reservoirs. To assess evolutionary selection for niche-specific traits, a genomic comparison of 749 P. aeruginosa strains from three environments (clinical, aquatic, and soil) was performed. The results showed that the environment does indeed exert selective pressure on specific traits. The high percentage of persistent genome, the lack of correlation between phylogeny and origin of the isolate, and the high intrinsic resistance indicate that the species has a high potential for pathogenicity and resistance, regardless of the reservoir. The flexible genome showed an enrichment of metal resistance genes, which could act as a co-selection of antibiotic resistance genes. In the plasmids, resistance genes were found in multigenic clusters, with the presence of a mobile integron being prominent. This integron was identified in several pathogenic strains belonging to distantly related taxa with a worldwide distribution, showing the risk of rapid evolution of resistance. These results provide a more complete understanding of the evolution of P. aeruginosa, which could help develop new prevention strategies.